How Motivation, Knowledge, And Technology Shape Investment Interest In The Sharia Capital Market - Dianah, Azimah; Fitri, Cut Dian; Haikal, Muhammad (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2025)
In the rapid development of information technology and the economy Currently, the capital market is very familiar to students. But the lack of awareness of the importance of investment for the future becomes the problem of a lack of investors (students) in investing in the capital market. The Islamic capital market is simply a place or means of meeting between demand and supply of short-term and long-term financial instruments. This research aims to analyze the influence of investment motivation, investment knowledge and technological progress on investment interest in the capital market sharia with research subjects of FEBI UIN Ar-Raniry Banda Aceh students. Testing the hypothesis using the validity test method, analysis multiple linear regression and classical assumption testing. Retrieval technique sample using stratified random sampling, with a sample that was taken by 100 students. The data used is primary data or direct data sourced from students who are in the location study. The results of the study found that motivated investment and technological progress have a positive and significant effect on the interest of FEBI students in investing in the Capital Market Sharia, while the investment knowledge variable has no significant effect on the interest of FEBI students partially. Next by Simultaneously all independent variables affect interest FEBI students in investing in the Islamic Capital Market.